Online footwear customization: experts’ overview - Oliveira, Nelson José Novais (2020)
The current era of valuing and sharing experiences results from the assertion of a consumer proudly eager to actively intervene in building his or her sphere of action. This emerging consumer trend is bringing closer and boosting the relationship between consumer and industry. strongly leveraged by new technologies and digital environments, blurring the boundaries between industry and consumer/user. This translates into a profound change in creation, production, and acquisition paradigms. More and more, footwear brands recognize the potential of online customization platforms. Thus, it is imperative to develop collaborative creation tools that can reduce the complexity of this process. To obtain critical information on this type of interfaces, a questionnaire was developed and applied to a group of experts. The objective was to obtain specific and exhaustive data on the researched reality and to contribute to the theoretical reflection of the collaborative design applied to online footwear customization.